Family Background and Parenting Characteristics of Young People with Methamphetamine Use Disorder in Northeastern Region of Thailand - Pinet Tatiwechakul1 ,Varisara Luvira2 , Akarapat Tayarajakul3, Wannaporn Phachantasein4 (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Drug abuse is an important medical problem which affects both the patient and society. This problem is rather common among young people in Thailand which family upbringing is one of the risk factors especially in the Northeastern region where prevalence of parental migration is the highest. Objective: The objective of this study was to examine family background and parenting characteristics of young people with methamphetamine use disorder as well as the association between factors related to family upbringing and the onset of substance use in these young people. Materials and Method: This cross-sectional descriptive study of young people between 18 and 24 years of age with methamphetamine use disorder who visited outpatient clinics in Thanyarak Udon Thani Hospital and Thanyarak Khon Kaen Hospital. 145 subjects were included to complete self-answer questionnaire that included demographic information, details on substance uses, family background and parenting characteristics. Results: The results showed 88.3% were male and the mean age of 21.22 years. The prevalence of parental migration during childhood was 30.34% (95%CI: 23.14, 38.61) while parental absence was 16.6%. Primary caregivers during childhood were either father or mother in 70.34% of the subjects. Data analysis found that having neither of parents as primary caregivers was associated with the onset of methamphetamine use before age of 18 years (p<0.5). Conclusion: Having one or both parents as childhood primary caregivers could reduce the risk of methamphetamine abuse among adolescents.